Impact of Ultrasonographic Findings on Cancer Detection Rate during Magnetic Resonance Image/ Ultrasonography Fusion-Targeted Prostate Biopsy - Jong Kil Nam; Won Hoon Song; Seung Soo Lee; Hyun Jung Lee; Tae Un Kim; Sung-Woo Park (The World Journal of Men's Health, 2023)
Purpose: To evaluate the impact of paired transrectal ultrasonography (TRUS) findings of index lesions identified by multiparametric magnetic resonance imaging (mpMRI) on the detection rate of clinically significant prostate cancer (csPCa, Gleason score ≥7) during MRI/US fusion-targeted biopsies. Materials and Methods: From 2019 to 2021, TRUS findings of paired index lesions were prospectively collected from MRI/ US cognitive (cTB, n=299) or program-assisted (pTB, n=294) fusion-targeted biopsies. csPCa detection rates according to the presence of a paired hypoechoic lesion (HoEL) and predictive factors for csPCa detection by targeted biopsy were evaluated. Results: Among 593 patients with visible lesions on upfront mpMRI (Prostate Imaging-Reporting and Data System score ≥3), 288 (48.6%) had paired HoELs on TRUS. The csPCa detection rates in targeted biopsy patients with and without paired HoELs were 56.3% and 10.5% (p<0.001), respectively. Detection rates in patients with and without paired HoELs in the peripheral zone were 65.0% and 14.5%, respectively, and in the transition zone, 37.4% and 8.2%, respectively. In the cTB cohort, a paired HoEL (OR=6.25; p<0.001) was an independent predictive factor for the detection of csPCa in the target core, but not in the pTB cohort (OR=1.92; p=0.107). Conclusions: During MRI/US fusion-targeted biopsy, csPCa detection rate was higher in patients with paired HoELs on TRUS than in those without it. After adjustment of the zonal location and mpMRI findings, the presence of paired HoELs is an independent predictive factor for csPCa detection in cTB, but not in pTB. Therefore, paired HoELs improve only the targeting of visually estimated biopsies.